Managing infectious diarrhea among young children in community pharmacies in Saudi Arabia and the implications for AMR - Alnezary, Faris S.; Alamri, Amira R.; Alrehaili, Rafa D.; Alnizari, Dina S.; Alzahrani, Fahad; Mahmoud, Mansour; Almutairi, Masaad S.; Kurdi, Amanj; Godman, Brian (Frontiers in Pediatrics, 2024)
Introduction: Diarrhea remains a major global health issue for children under five, contributing substantially to morbidity and mortality. Community pharmacists play a pivotal role in the management of these children; however, their competence in managing childhood diarrhea in Saudi Arabia is under-researched. This is important to ensure optimal patient care. Method: Simulated patients (SPs) presenting with three pediatric diarrhea scenarios were used to evaluate pharmacists' practice in terms of their counselling, history taking, over-the-counter (OTC) prescribing, medication instructions, diet/fluid advice, and/or information provision. Pharmacists' practice was categorized into adequate, less adequate, and poor. Results: 182 community pharmacists, primarily male and non-Saudi, participated in the study, of which 60% were in chain pharmacies. Only 5% showed adequate practice in currently managing pediatric diarrhea. Of the 182 simulated patient visits, 62% received medication in all three scenarios and 20% were referred to physicians, with 16% of pharmacists failing to provide any form of intervention. The main medications recommended were kaolin (34%), pectin (34%) and metronidazole (11%). While most pharmacists (86%) asked about the patient's identity and age, 15% provided incorrect management information, 16% failed to provide guidance on the prescribed medicines, and 18% dispensed antimicrobials without a valid prescription. Conclusion: A high level of inadequate management of pediatric diarrhea in Saudi Arabia was observed. This highlights the need for extensive training to improve community pharmacists' practice in service delivery including providing counselling and advice on the appropriate management of childhood diarrhea. The latter is particularly important to reduce antimicrobial resistance.